Conflict Security and The Right to Development (Zien Journal of Social Sciences and Humanities, 2021)
Conflicts are inevitable in human relations; they have been considered a regular part of human existence. The African continent is plagued with a plethora of conflicts, reasons why most scholars have referred to it as the home of conflict. The right to development is a fundamental human right and a third generation right. On the whole this paper presents an examination of conflict security, causes of conflict security and their effects on the right to development, the nexus between conflict security and development within the paradigm of the human security, generic and the human rights-based approach. As a way out of the predicament of wars and conflicts that has affected Africa, it is apt to offer some valuable suggestions based on a thorough analysis of the causes of the problem. In this wise, two major broad solutions may be experimented with intent to bail Africa out of recurrent conflicts and wars. These are committed and sincere leadership and eradication of poverty